Detection and Verification of QTL for Salinity Tolerance at Germination and Seedling Stages Using Wild Barley Introgression Lines - Mohammed Abdelaziz Sayed (MDPI AG, 2021)
Salinity is one of the major environmental factors that negatively affect crop development, particularly at the early growth stage of a plant and consequently the final yield. Therefore, a set of 50 wild barley (Hordeum vulgare ssp. spontaneum, Hsp) introgression lines (ILs) was used to detect QTL alleles improving germination and seedling growth under control, 75 mM, and 150 mM NaCl conditions. Large variation was observed for germination and seedling growth related traits that were highly heritable under salinity stress. In addition, highly significant differences were obtained for five salinity tolerance indices and between treatments as well. A total of 90 and 35 significant QTL were identified for ten investigated traits and for tolerance indices, respectively. The Hsp introgression alleles are involved in improving salinity tolerance at forty (43.9%) out of 90 QTL including introgression lines S42IL-109 (2H), S42IL-116 (4H), S42IL-132 (6H), S42IL-133 (7H), S42IL-148 (6H), and S42IL-176 (5H). Interestingly, seven exotic QTL alleles were successfully validated in the wild barley ILs including S42IL-127 (5H), 139 (7H), 125 (5H), 117 (4H), 118 (4H), 121 (4H), and 137 (7H). We conclude that the barley introgression lines contain numerous germination and seedling growth-improving novel QTL alleles, which are effective under salinity conditions.